Soucasné moznosti diagnostiky a lécby anémie chronických chorob - Scudla, V; Adam, Z; Scudlová, M (Vnitrni lekarstvi, 2001)
The article deals with contemporary views on anaemia associated with chronic diseases. The authors present the definition of this nosological unit, draw attention to its high incidence in clinical practice and fact that it is frequently mistaken for iron deficiency anaemia. The authors submit a review of the most frequent diseases which cause the development of this type of anaemia and analyze the role of activation of the system of cellular immunity, the monocyte-macrophage system, agents of the cytokine network in inhibition of proliferation and differentiation of erythroid precursors, reduced production of endogenous erythropoietin with a reduced sensitivity of erythroid progenitor cells to its action and impaired iron homeostasis and inhibition of its reutilization. Special attention is devoted to diagnostic and differential diagnostic criteria in relation to other types of anaemia caused by impaired haeme synthesis and some secondary multifactorially conditioned types of anaemia. More detailed attention is paid to the diagnostic value of evaluating serum levels of soluble transferrin receptors and explanation of the asset of calculation of the transferrin receptor/ferririn index as a sensitive indicator of latent sideropenia as well as the Fe-absorption test using low oral iron doses. Part of the paper is also an account of contemporary possibilities of treatment including the use of the recombinant form of human erythropoietin, and attention is drawn to the unsuitability and pitfalls of iron therapy in this type of anaemia.
Keywords: chronická nemoc; diferenciální diagnóza; Diagnosis, Differential; Humans; lidé; Anemia; anemie; Chronic Disease